Design of The Digital Sphygmomanometer Using Pressure Sensor - Yuwono, Tito; Irawan, Erwin Yan; Kusriyanto, Medilla; Isti’anah, Siti (LIPI Press, Anggota IKAPI, 2014)
Blood pressure measurement is a very important activity. Blood pressure determines the strength of blood flow circulating in the body. If blood pressure is too high or too low, it will cause vital impact and even lead to death. The measuring of blood pressure commonly uses mercury sphygmomanometer. Disadvantages of this instrumention are users should have good hearing and sight, depending on the sensitivity of the stethoscope, and not user-friendly. In this paper, the writers will discuss the design and development of digital blood pressure instrumentation that is user-friendly. Some of the components used in this instrumentation are MPX5050GP pressure sensor, comparator, voice circuit, and LCD circuit. The result of blood pressure measurement is displayed on the LCD and sound. With these features, user can use this instrumentation easily. The performance of this intrument was tested by comparing it with mercury sphygmomanometer. The accuracy of this instumentation is 99.33%. The advantages of this instrumentation are it doesnâ€™t depend on the sensitivity of stethoscope and the level of blood pressure can be viewed and heard directly on the LCD and Speaker.Â Keywords: Blood pressure; Digital sphygmomanometer; Pressure sensor; user-friendly.